Evolution of a tissue-specific splicing network. - Taliaferro, J.M.; Alvarez, N.; Green, R.E.; Blanchette, M.; Rio, D.C. (Genes & Development, 2011)
Alternative splicing of precursor mRNA (pre-mRNA) is a strategy employed by most eukaryotes to increase transcript and proteomic diversity. Many metazoan splicing factors are members of multigene families, with each member having different functions. How these highly related proteins evolve unique properties has been unclear. Here we characterize the evolution and function of a new Drosophila splicing factor, termed LS2 (Large Subunit 2), that arose from a gene duplication event of dU2AF(50), the large subunit of the highly conserved heterodimeric general splicing factor U2AF (U2-associated factor). The quickly evolving LS2 gene has diverged from the splicing-promoting, ubiquitously expressed dU2AF(50) such that it binds a markedly different RNA sequence, acts as a splicing repressor, and is preferentially expressed in testes. Target transcripts of LS2 are also enriched for performing testes-related functions. We therefore propose a path for the evolution of a new splicing factor in Drosophila that regulates specific pre-mRNAs and contributes to transcript diversity in a tissue-specific manner.